HASIL TES KOLESTEROL TOTAL ANTARA ALAT POCT DAN FOTOMETER PADA PASIEN HIPERTENSI DI POLIKLINIK DITJEN KI KEMENKUMHAM - Heru Setiawan; Fitriya Nurbayati (Jurnal Fisioterapi dan Kesehatan Indonesia, 2022)
Total cholesterol is a good indicator to predict whether a person has a high risk of developing hypertension. The higher the total cholesterol level, the higher the possibility of hypertension. Cholesterol examinations in several clinic laboratories generally uses a photometer and Point of Care Testing (POCT). These two examination methods have several differences, each of which has advantages ang disadvantages. Although in terms of the cost of examination with a photometer, is more expensive and take longer to work, but has good precision and accuracy, so is used as a reference method for cholesterol examination to help diagnose treatment. Meanwhile, the examination with the POCT tool is only for monitoring total cholesterol levels. The purpose of this study was to know whether or not there was a significant difference between the results of total cholesterol examination using the tools POCT with the photometer in hypertensive patient at Polyclinic Directorate General Intellectual Property, Ministry of Law and Human Right. The study was conducted in May-June 2022 as many as 70 samples. The research design used is categorical-numerical unpaired analysis with an experimental approach to data processing using the mean difference test the average of 2 independent sample group t-test. The result showed that the average total cholesterol level with a photometer in hypertensive patients was 214.97 mg/dL and on the POCT 232.66 mg/dL. Significant difference test was obtained value = 0.003, (p < 0.05) which indicated there was a significant difference between the result of the examination total cholesterol between the POCT device and the photometer. Keywords: Total Cholesterol, Photometer, POCT, Hypertension